PENTINGNYA ASI UNTUK IBU BEKERJA YANG MENYUSUI DI MLAJAH BANGKALAN - Qurrotu Aini (STIKES NGUDIA HUSADA MADURA, 2021)
The cause of the emergence of nutritional problems in children under five is influenced by many interrelated factors. It is directly influenced by several things, namely the child does not get enough nutritious food at the age of five, the child does not get adequate nutritional care and the child suffers from an infectious disease. One of the causes of malnutrition is that babies do not receive full breast milk until the first 6 months of age. The method used to carry out community service is by collecting data on the number of breastfeeding mothers in Mlajah Bangkalan. The targets of this program are all breastfeeding mothers in Mlajah Bangkalan and one of their closest people (husband or parent). Health workers will be assisted or accompanied by cadres to run the ASI class program. As is well known, the role of the closest family is very important in providing motivation to breastfeeding mothers. Not only families, midwife assistants, namely cadres are also involved in providing education. During the process of the ASI Class activities program, which consists of a cadre formation program, counseling, giving lactation medians, and the entire program runs smoothly. All preparations have been made by the team, the village youth organization and the village midwives involved. The drawbacks that may occur in the implementation of the ASI Class program are the activities of the ASI Class program in conjunction with the daily activities of mothers so that there are several programs that must be rescheduled.